Victims of Sexual Abuse with Child Pregnancy Case Report - Tunçez, Ferhat Turgut; Ersen, Gülden; Kılıççıoğlu, Doğu Barış; Küçük, Zeynep Sağlık; Tokdemir, Mehmet (The Bulletin of Legal Medicine, 2022)
Sexual crimes are an important forensic and medical problem that creates permanent traumas primarily on the victims. In our study, we aimed to present three cases under the age of 15 who were conceived after sexual abuse. Our first case was a 13-years-old with a pregnancy as a result of abuse without penetration. Our second case was a 12-years-old, and as a result of incest. Our third case; a 14-years-old, and it was found that she was 24 weeks pregnant in her examination. Forensic and medical problems have arisen due to reasons such as the fact that our sexual abuse cases were at childhood and even became pregnant as a result of this abuse, the abuse was due to incest, abortion could not be performed as a result of delayed applications. In addition, it should be kept in mind that pregnancy can occur without penetration in child abuse cases.
Keywords: child abuse; pregnancy; incest; abortion